Stem cells therapy for treatment of ocular disorders - Sivan, Padma Priya (Hindawi Publishing Corporation, 2016)
Sustenance of visual function is the ultimate focus of ophthalmologists. Failure of complete recovery of visual function and complications that follow conventional treatments have shifted search to a new form of therapy using stem cells. Stem cell progenitors play a major role in replenishing degenerated cells despite being present in low quantity and quiescence in our body. Unlike other tissues and cells, regeneration of new optic cells responsible for visual function is rarely observed. Understanding the transcription factors and genes responsible for optic cells development will assist scientists in formulating a strategy to activate and direct stem cells renewal and differentiation. We review the processes of human eye development and address the strategies that have been exploited in an effort to regain visual function in the preclinical and clinical state. The update of clinical findings of patients receiving stem cell treatment is also presented.